A case of massive saddle pulmonary embolism and benign tracheal stenosis in a patient with COVID‐19 infection. Issue 11 (4th October 2021) - Nehme, Ralph; Fleifel, Mohamad; Abou Khalil, Melissa; Al Dailaty, Ali
Abstract: Since December 2019, the novel coronavirus disease 2019 (COVID‐19) outbreak that started in Wuhan, China, has become a global pandemic affecting millions of people around the globe. These patients are prone to a number of complications either related to their disease or to the different treatment modalities. Pulmonary embolism (PE) and benign post‐intubation tracheal stenosis (BTS) are among these complications. In this study, we report the case of a patient with a recent COVID‐19 infection that got complicated by a massive PE as well as a BTS. Abstract : We report the case of a patient with a recent coronavirus disease 2019 (COVID‐19) infection that got complicated by a massive pulmonary embolism as well as benign post‐intubation tracheal stenosis.